Culture Environment Affects PLB or Shoot Proliferation Rate of a Phalaenopsis Orchid New Type: Proposing a Shorter Breeding Scheme - Widiarsih, Sasanti; Dwimahyani, Ita; Budiarto, Kurniawan; Utami, Dwinita Wikan; Muljono, Djoko; Sanjaya, Liauw Lia (AGRIVITA Journal of Agricultural Science, 2026)
The global trade value of Phalaenopsis is still promising; therefore, the prospects for future orchid agribusiness remain widely open. As a part of Indonesian new-variety registration, seeds of the registered variety must meet a quality standard within two years. In addition, a reliable, large-scale supply of uniform seeds is vital to the industry. Research on clonal propagation of Phalaenopsis orchids has been studied for the last three years, but the proliferation rate of PLBs remains unsatisfactory. This might be related to the relatively low temperature of the micro environment. Placing the cultures in the 'acclimatization' room provided with a conducive micro-environment resulted in a significant increase in PLBs/shoots (30-50/explant). It is assumed that the proliferation rate of PLBs/shoots can be increased by setting the optimum exposure time. Two temperature regimes were implemented; the first was a 29-32°C light condition (14 hours) followed by a 22–25°C 10-hour dark period, and the second was the opposite: cooler temperatures during the 14-hour light period (22-24°C) and warmer temperatures during the 10-hour dark period (25-28°C). In this paper, we present the results of an extensive three-year study on the multiplication of the Phalaenopsis orchid, leading to a much shorter orchid crossbreeding scheme.